2012
DOI: 10.5402/2012/851097
|View full text |Cite
|
Sign up to set email alerts
|

Diagnoses of Patients with Severe Subjective Health Complaints in Scandinavia: A Cross Sectional Study

Abstract: Background. A diagnosis is the basis of medical action, the key to various social privileges and national sick leave statistics. The objectives of this study were to investigate which diagnoses general practitioners in Scandinavia give patients with severe subjective health complaints, and what kind of treatments they suggested. Methods. One hundred and twenty-six self-selected general practitioners in Scandinavia diagnosed nine patients, presented as video vignettes, in a cross-sectional study. The main outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…There are at least two reasons that treatment can have a limited effect for non-surgical patients. Some patients have diffuse musculoskeletal pain and symptoms, and it can be difficult to give the correct medical diagnosis (Maeland et al 2012). Treatment is then prone to trial and error without proper medical effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are at least two reasons that treatment can have a limited effect for non-surgical patients. Some patients have diffuse musculoskeletal pain and symptoms, and it can be difficult to give the correct medical diagnosis (Maeland et al 2012). Treatment is then prone to trial and error without proper medical effect.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the lack of clear evidence that treatment reduces length of sick leave, there is also a question of given a correct medical diagnosis as the basis of medical action. Maeland et al (2012) analyse which diagnosis GPs give patients with subjective health complaints, and what kind of treatments they suggested. They find that GPs give a large variety of diagnosis and treatment to the same type of patient, indicating how difficult it can be to give proper treatment to people with diseases of the musculoskeletal system.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that individuals suffering from medically unexplained syndromes experience not being taken seriously within the health care system and often report disbelief and lack of support from their communities . This fact may cause severe problems for individuals with these syndromes because APP and social security benefits are not readily granted without a known biomedical diagnosis . Issues of legitimacy may in turn contribute to elevated distress and suffering and an aggravation of the physical symptoms .…”
Section: Contextual Settingmentioning
confidence: 99%
“…Issues of legitimacy may in turn contribute to elevated distress and suffering and an aggravation of the physical symptoms . However, often, the experienced symptoms are attributed to psychological factors leaving these individuals to cope with their situation on their own …”
Section: Contextual Settingmentioning
confidence: 99%
“…It was based on simulated, video-recorded consultations with a common denominator: a simulated patient presenting so-called subjective health complaints (SHC) to a GP [6]. Such a presumably objective approach to human beings may in itself represent an ethically questionable reduction of both doctors and patients for several reasons [7].…”
mentioning
confidence: 99%